Complexation study of Schiff base ligand: pyridin-2-ylimino methyl naphthanol with Co+2, Mn+2 and Ni+2 ions in solid and solution phase. Issue 15 (2nd August 2016) - Sagar, Shipra; Mongal, Binitendra Naath; Dutta, Abhijit; Mondal, Paritosh; Lewis, William; Saba, Nadis; Naskar, Subhendu
Abstract: Schiff base pyridin-2-ylimino methyl naphthanol (HL) was synthesized and characterized by spectroscopic (FTIR, ESIMS, and NMR) techniques. The ligand was reacted with perchlorate salts of Mn +2, Co +2, and Ni +2 . ESIMS mass spectra indicate the formation of mononuclear complex ML2 for all three complexes. CoL2 crystallizes in P 2 1 / n space group, adopting a distorted tetrahedral geometry where Co is in a N2 O2 donor environment. Structure of the Co complex was optimized by DFT calculation. Solution-phase complexation between the ligand and the three metals ions: Mn +2, Co +2, and Ni +2 (pH 7.2 in tris buffer), in CH3 CN–H2 O was performed spectrophotometrically by UV–vis spectral study. Job's plot from each titration suggests a 1 : 2 metal to ligand combination. The association constants for the formation of ML2 are as follows: Mn (19.80 × 10 3 M −1 ), Co (14.54 × 10 3 M −1 ) and Ni (19.04 × 10 3 M −1 ). Abstract :